2014
DOI: 10.1136/jnnp-2014-309236.1
|View full text |Cite
|
Sign up to set email alerts
|

National Audit of Seizure Management in Hospitals 2 (Nash2)

Abstract: Background NASH1 (National Audit of Seizure management in UK Hospitals) collected data in 2011 and fed back in 2012. It identified significant shortfalls and variability in the way that care was provided. Here we report the second round-NASH2. Methods NASH2 assessed the prior, immediate, and onward care of patients attending Emergency Departments with seizures. Sites provided anonymous data on 30 consecutive cases via a web-based database between June and September 2013. Results Data were collected from over 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In the current study people with primarily alcohol problems were excluded as a different nurse specialist service is responsible for their management at hospital. However, the NASH study 52 found that epilepsy with alcohol overuse was a frequent correlate of ED attendance. In the current study predictors of frequent attendance were lower confidence in managing epilepsy, a higher number of prescribed AEDs, more felt stigma, a higher number of baseline ED visits, greater seizure frequency and higher levels of depression and anxiety.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In the current study people with primarily alcohol problems were excluded as a different nurse specialist service is responsible for their management at hospital. However, the NASH study 52 found that epilepsy with alcohol overuse was a frequent correlate of ED attendance. In the current study predictors of frequent attendance were lower confidence in managing epilepsy, a higher number of prescribed AEDs, more felt stigma, a higher number of baseline ED visits, greater seizure frequency and higher levels of depression and anxiety.…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with process evidence from a national audit suggesting that ED use offers little added value to care. 52 Using regression analysis we found that, in descending order of importance, less knowledge, more felt stigma, poorer medication management and greater seizure frequency predicted emergency visits before entering the study.…”
Section: The Characteristics Of People With Epilepsy Who Attend the Ementioning
confidence: 91%
See 3 more Smart Citations